Human umbilical cord mesenchymal stem cells regulate immunoglobulin a secretion and remodel the diversification of intestinal microbiota to improve colitis - Liu, Airu; Wang, Xing; Liang, Xiaonan; Wang, Wenxin; Li, Chenyang; Qian, Jiaming; Zhang, Xiaolan (Frontiers in Cellular and Infection Microbiology, 2022)
Background Mesenchymal stem cell (MSC) therapy has emerged as a promising novel therapeutic strategy for managing inflammatory bowel disease (IBD) mainly via dampening inflammation, regulating immune disorders, and promoting mucosal tissue repair. However, in the process, the associated changes in the gut microbiota and the underlying mechanism are not yet clear. Methods In the present study, dextran sulfate sodium (DSS) was used to induce colitis in mice. Mice with colitis were treated with intraperitoneal infusions of MSCs from human umbilical cord mesenchymal stem cells (HUMSCs) and evaluated for severity of inflammation including weight reduction, diarrhea, bloody stools, histopathology, and mortality. The proportion of regulatory T cells (Tregs) and immunoglobulin A-positive (IgA+) plasmacytes in gut-associated lymphoid tissue were determined. The intestinal and fecal levels of IgA were tested, and the proportion of IgA-coated bacteria was also determined. Fecal microbiome was analyzed using 16S rRNA gene sequencing analyses. Results Treatment with HUMSCs ameliorated the clinical abnormalities and histopathologic severity of acute colitis in mice. Furthermore, the proportion of Tregs in both Peyer’s patches and lamina propria of the small intestine was significantly increased. Meanwhile, the proportion of IgA+ plasmacytes was also substantially higher in the MSCs group than that of the DSS group, resulting in elevated intestinal and fecal levels of IgA. The proportion of IgA-coated bacteria was also upregulated in the MSCs group. In addition, the microbiome alterations in mice with colitis were partially restored to resemble those of healthy mice following treatment with HUMSCs. Conclusions Therapeutically administered HUMSCs ameliorate DSS-induced colitis partially via regulating the Tregs–IgA response, promoting the secretion of IgA, and facilitating further the restoration of intestinal microbiota, which provides a potential therapeutic mechanism for HUMSCs in the treatment of IBD.